PENGENALAN KUALITAS PELAYANAN PADA UKM SHINTYA’S KITCHEN DI JAMBI - Rodhiah; Nuraisyah, Iis; Aisyah , Anggun (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
Providing quality service is very important in achieving a level of customer satisfaction. Every company, both large and small, must be able to improve the quality of service to consumers, so that the company can maintain business and face more and more competitors. Pkm's activity partner is Shintya's Kitchen which is a business in the culinary field in the Jambi area. In running a business, partners have problems in terms of improving the quality of service. Knowledge of the quality of service is not yet fully understood by partners. Therefore, the purpose of PKM is to help overcome partner problems in understanding more about the quality of service that partners must pay attention to in running a business. The activity method is carried out through training delivered by the chairman and student members online through ZOOM meetings. The meter presented includes: elaboration of the service quality dimension model, namely Responsiveness, Reliability, Assurance, Emphaty and Tangibles. The results of the activity show that it has been carried out well and runs smoothly, partners can understand the quality of service, as evidenced by the results of the evaluation of partner answers 100% understanding the material that has been submitted by the PKM Team leader. Ultimately the PKM program has helped partners understand more about the quality of service, which can be applied to customers. In the future, partners can maintain customer satisfaction, which in turn can become loyal customers.